The Nexus Between Health and Economic Growth: Empirical Evidence from Indonesia - Mochammad Yusuf; Avi Budi Setiawan (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2022)
The controversial debate about the relationship between health and economic growth nexus has become one of the most contentious issues in the last two decades of scientific development. The inconsistency of research results that occur makes this hypothesis very interesting to study, especially in developing countries such as Indonesia. This study aims to determine the relationship between health variables such as healthcare expenditure, human development index, life expectancy, and mortality on economic growth with the Indonesian case study as the object of analysis. This study uses secondary data from Indonesia in the period 1985-2021 using the Engle-Granger Error Correction Model and Granger Causality. Based on the estimation of the Engle-Granger Error Correction Model, both in the long term and in the short term, all health variables have a significant influence on economic growth. To prove the causal relationship between health variables and economic growth, a causality granger analysis was used, it was found that healthcare expenditure had a causal (bidirectional) relationship with economic growth. Another causal relationship is also found in the human development index, the rest there is a unidirectional relationship between mortality and economic growth. This finding proved that health plays a crucial role on economic growth. Therefore, the government must be able to take several policies to improve the quality of public health including: prioritize development budget allocations for health infrastructure, implementing cash-transfer and health subsidies program to reduce cost-barriers that limiting healthcare access of poor people.